PROFILE CHARACTERISTICS OF SHEEP FARMERS: A SURVEY IN KANCHEEPURAM DISTRICT OF TAMIL NADU - Thilakar , P; Krishnaraj, R (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The present survey was conducted to identify the profile characteristics of sheep farmers. Uthiramerur block of Kancheepuram district in Tamil Nadu was selected purposively and the data pertaining to socio-economic profile were collected by pre-tested structured interview schedule from 120 farmers of randomly selected 12 villages. The study revealed that about one-half (40.83 %) of the respondents belonged to old age group and 64.17% had primary to secondary level of education, while 35.83% were illiterates. Majority of the farmers pursued sheep farming as main occupation with large flock size and their income ranged from Rs.12001 to 24000/- with experience of 11 - 20 years in Sheep farming. Greater part of the respondents possessed medium extension agency contact, medium mass media exposure, economic motivation, credit behaviour and has not participated in any formal organisation.